Integrating Cultural Rights into Human Rights Frameworks: Re-Regulating Tourism and Copyright Law in Indonesia - Hari Sutra Disemadi (Human Rights et Justicia, 2025)
The recognition of cultural rights as an integral component of human rights has gained increasing attention in contemporary legal discourse, particularly in multicultural and tourism-oriented countries such as Indonesia. This study examines the integration of cultural rights into human rights frameworks through the re-regulation of tourism and copyright law in Indonesia. The research aims to analyze how existing legal instruments accommodate the protection of cultural expressions while simultaneously responding to the commercialization of culture within the tourism industry. Employing a normative juridical method with statutory and conceptual approaches, this study analyzes national regulations on human rights, tourism, and copyright, as well as relevant international human rights instruments. The findings indicate that although Indonesian law formally acknowledges cultural rights as part of human rights, sectoral regulations governing tourism and copyright remain fragmented and often prioritize economic interests over cultural sustainability and community rights. This regulatory gap has led to the commodification of cultural heritage without adequate legal safeguards for indigenous and local communities. The study argues that integrating cultural rights into human rights frameworks requires a reorientation of tourism and copyright law toward a rights-based approach that emphasizes participation, consent, and equitable benefit-sharing. Such integration is essential to ensure that cultural preservation and economic development proceed in a balanced and just manner within Indonesia’s pluralistic society. Pengakuan terhadap hak budaya sebagai bagian yang tidak terpisahkan dari hak asasi manusia semakin memperoleh perhatian dalam diskursus hukum kontemporer, khususnya di negara multikultural dan berbasis pariwisata seperti Indonesia. Penelitian ini mengkaji integrasi hak budaya ke dalam kerangka hak asasi manusia melalui pengaturan ulang hukum pariwisata dan hukum hak cipta di Indonesia. Tujuan penelitian ini adalah untuk menganalisis sejauh mana instrumen hukum yang ada mampu melindungi ekspresi budaya sekaligus merespons praktik komersialisasi budaya dalam sektor pariwisata. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan konseptual, dengan menelaah regulasi nasional di bidang HAM, pariwisata, dan hak cipta, serta instrumen HAM internasional yang relevan. Hasil penelitian menunjukkan bahwa meskipun hukum Indonesia secara normatif telah mengakui hak budaya sebagai bagian dari HAM, regulasi sektoral di bidang pariwisata dan hak cipta masih bersifat terfragmentasi dan cenderung mengedepankan kepentingan ekonomi dibandingkan keberlanjutan budaya dan perlindungan hak masyarakat lokal. Kondisi ini berimplikasi pada terjadinya komodifikasi warisan budaya tanpa perlindungan hukum yang memadai. Penelitian ini menegaskan bahwa integrasi hak budaya ke dalam kerangka HAM menuntut reorientasi hukum pariwisata dan hak cipta menuju pendekatan berbasis hak yang menekankan partisipasi, persetujuan, dan pembagian manfaat yang adil.